2006
DOI: 10.1158/0008-5472.can-05-4288
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oncogenes to Improve Breast Cancer Chemotherapy

Abstract: Despite recent advances in treatment, breast cancer remains a serious health threat for women. Traditional chemotherapies are limited by a lack of specificity for tumor cells and the cell cycle dependence of many chemotherapeutic agents. Here we report a novel strategy to help overcome these limitations. Using triplex-forming oligonucleotides (TFOs) to direct DNA damage site-specifically to oncogenes overexpressed in human breast cancer cells, we show that the effectiveness of the anticancer nucleoside analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…We have used TFOs targeted to the c-MYC gene to stimulate repair synthesis in the presence of an antitumor antimetabolite, gemcitabine, to increase its incorporation into DNA. We found that when used in combination, c-MYC-specific TFOs significantly increased the effectiveness of gemcitabine in inhibiting the growth of human breast tumor cells [33].…”
Section: Directing Site-specific Dna Damagementioning
confidence: 84%
“…We have used TFOs targeted to the c-MYC gene to stimulate repair synthesis in the presence of an antitumor antimetabolite, gemcitabine, to increase its incorporation into DNA. We found that when used in combination, c-MYC-specific TFOs significantly increased the effectiveness of gemcitabine in inhibiting the growth of human breast tumor cells [33].…”
Section: Directing Site-specific Dna Damagementioning
confidence: 84%
“…It is referenced in the literature under other names such as targeted nucleotide exchange, chimeraplasty, oligonucleotidemediated gene editing, chimeric oligonucleotidedependent mismatch repair, oligonucleotide-mediated gene repair, triplex-forming oligonucleotides induced recombination, oligodeoxynucleotide-directed gene modification, therapeutic nucleic acid repair approach, targeted gene repair (see e.g. Andersen et al, 2002;Christensen et al, 2006;Cole-Strauss et al, 1999;de Semir and Aran, 2006;Igoucheva et al, 2006;Zhang et al, 1998).…”
Section: What Is Oligonucleotide-mediated Mutagenesis?mentioning
confidence: 99%
“…Last but not least, the technique seems to offer opportunities for the future in the field of human gene therapy to correct point mutations, for instance in monogenic inherited diseases and cancer (Christensen et al, 2006;de Semir and Aran, 2006;Kmiec, 2003;Wu et al, 2001). The therapy using oligonucleotides or RNA/DNA chimeras can result in a fraction of cells in which the wild-type gene can be restored.…”
Section: Mammalsmentioning
confidence: 99%
“…The clinical therapeutic regimens for breast cancer include resection, chemotherapy, radiotherapy and biological therapy [2]. However, the treatments of breast cancer are commonly unsuccessful, because of its secondary recurrence, metastasis and drug resistance [3,4]. The chemotherapy drug doxorubicin (DOX), which is an anthracycline anti-cancer drug, has been widely used to treat breast cancer, leukemia and lung cancer by inhibiting DNA topoisomerase II and intercalating double strand DNA [5,6].…”
Section: Introductionmentioning
confidence: 99%